Triple Pelvic Osteotomy Fixed with Lag Screw for the Treatment of Pelvic Canal Stenosis in Five Cats - Cinti, Filippo; Cavaliere, Leonardo; Degna, Matteo Tommasini; Rossi, Federica; Pisani, Guido (Veterinary and Comparative Orthopaedics and Traumatology, 2020)
Objective The aim of this study was to describe the technique and the clinical outcome of cats with obstipation as a result of pelvic canal narrowing, treated using an alternative triple pelvic osteotomy technique.Methods Five cats with obstipation as a result of pelvic canal narrowing due to pelvic fracture malunion or secondary hyperparathyroidism were treated by triple pelvic osteotomy. After performing the iliac osteotomy and medial partial cortical debridement (4/5 cases), the pelvic canal was widened by moving the caudal fragment of the ilium to the lateral aspect of the cranial fragment. The iliac fragments were fixed by a 2.7-mm lag screw (5/5 cases) and an additional 2 Kirschner wires 0.8 mm (1/5 cases).Results The radiographic examination immediately postoperatively and 8 weeks postoperatively showed a mean pelvic canal enlargement of 20% (range 7–38%). Minor complication occurred in one case; this resolved 15 days postoperatively without any treatment. Complications and recurrence of obstipation did not occur during the final follow-up, ranging between 5 months and 1 year in any of these cases.Clinical Significance The use of lag screw fixed triple pelvic osteotomy resulted in widening of the pelvic canal and led to a satisfactory outcome with no major complications. This technique is fast, requires no expensive implants and it is relatively straightforward. Further cases are required to determine the success and complication risk of the procedure.
Keywords: pelvic canal stenosis; triple pelvic osteotomy; cat; obstipation